The Relationship of Stress Level With Premenstrual Syndrome on Midwifery Students at Akbid Bandung - Triswanti, Triswanti; Herawati, Nurul; Septiani, Nurnisa (Riviera Publishing, 2024)
The prevalence of STDs in several regions in Indonesia shows different results. In South Jakarta, it shows that 45% of vocational school students experience PMS. In Kudus, the prevalence of PMS in Midwifery Academy students was found to be 45.8%. In Padang, 51.8% of high school students experienced PMS, while in Purworejo, the prevalence of PMS was 24.6% (Pratita & Margawati, 2013). Differences in the incidence of premenstrual syndrome (PMS) between women are usually caused by several factors including: stress, increasing age, poor eating patterns and nutritional status (Sukarni and Wahyu, 2013). To find out the relationship between stress levels and premenstrual syndrome in midwifery students at AKBID Bandung. This type of research is analytical research using a cross sectional design. The sample in this study were all female students of AKBID Bandung, Level II Regular Bachelor of Applied Midwifery Study Program, namely 48 female students. The sampling technique in this study was total sampling with a total sample of 48 female students. Data analysis used the chi-square test with a 95% confidence level (?=0.05). There was no association between stress levels and premenstrual syndrome (PMS) (?value = 0.733). The other factors of premenstrual syndrome include family history, age, lack of exercise, lack of vitamins and minerals, too much salt consumption, drinking a lot of coffee (Nugroho &; Utama, 2014). There was no significant association between stress levels and the incidence of premenstrual syndrome (PMS). This is because individuals who experience premenstrual syndrome are not only caused by stress factors, but also there are other supporting factors.